Avoiding Mistakes in Drone Usage in Participatory Mapping: Methodological Considerations during the Pandemic - Naufal Naufal; Andi Asriadi; Sutrisno Absar (Forestry Faculty, Universitas Hasanuddin, 2022)
Participatory mapping has continued to evolve with the onset of new methodologies and technology. Conventional methods for sketching have now expanded to incorporate the use of drone imagery and other sophisticated mapping approaches as a base map. However, the use of ultra-high resolution drone imagery does not mean that it will facilitate more participatory processes nor improve the quality of data and uses of information. Indeed, it has long been known that ultra-high spatial resolution can cause misinterpretation. During COVID-19, innovations are emerging to apply more remote technologies in participatory mapping. Mobility concerns, requirements, and preferences for physical distancing discourages active participation of local communities and are especially complex in contexts involving Indigenous People. This paper specifically explores the mistakes that can arise from over-reliance on employing drones as a tool in participatory mapping methods. This paper is based on a case study of participatory mapping conducted at 43 villages (around forest area) of Central Sulawesi Province and West Sulawesi Province. The participatory mapping was carried out by the Sulawesi Community Foundation (SCF) from 2019-2021. The result of the study found at least six signs of potentially negative outcomes from the use of ultra-high resolution drone imagery, starting from disorientation, misperception over the periods of drone acquisition, homogeneous land cover conditions, similar types of plants, numerous signs of nature, and labeling affixed on map. We also encourage the development of ultra-high-resolution drone imagery to take place under certain conditions and see its role as an interpretation dictionary or as a targeted tool in local contexts. In addition, we found that the level of active participation in participatory mapping during the Pandemic was higher than before the pandemic but requires some improvisations in meeting design